Antimicrobial stewardship perspectives from a New York City hospital during the COVID-19 pandemic: Challenges and opportunities. (5th February 2021) - Kubin, Christine J; Loo, Angela S; Cheng, Jennifer; Nelson, Brian; Mehta, Monica; Mazur, Shawn; So, Wonhee; Calfee, David P; Singh, Harjot K; Greendyke, William G; Simon, Matthew S; Furuya, E Yoko
Abstract: Purpose: To share challenges and opportunities for antimicrobial stewardship programs based on one center's experience during the early weeks of the coronavirus disease 2019 (COVID-19) pandemic. Summary: In the spring of 2020, New York City quickly became a hotspot for the COVID-19 pandemic in the United States, putting a strain on local healthcare systems. Antimicrobial stewardship programs faced diagnostic and therapeutic uncertainties as well as healthcare resource challenges. With the lack of effective antivirals, antibiotic use in critically ill patients was difficult to avoid. Uncertainty drove antimicrobial use and thus antimicrobial stewardship principles were paramount. The dramatic influx of patients, drug and equipment shortages, and the need for prescribers to practice in alternative roles only compounded the situation. Establishing enhanced communication, education, and inventory control while leveraging the capabilities of the electronic medical record were some of the tools used to optimize existing resources. Conclusion: New York City was a unique and challenging environment during the initial peak of the COVID-19 pandemic. Antimicrobial stewardship programs can learn from each other by sharing lessons learned and practice opportunities to better prepare other programs facing COVID-19 case surges.